Phosphorus-modified cobalt tungstate difunctional electrode material, preparation method thereof and application of phosphorus-modified cobalt tungstate difunctional electrode material in water electrolysis hydrogen production
By synthesizing phosphorus-modified cobalt tungstate nanoparticles on a nickel foam substrate, the problems of cross-interference and low activity of transition metal electrocatalysts were solved, efficient water electrolysis and hydrogen production performance was achieved, cost was reduced and stability was improved.
Patent Information
- Application Number
- CN202511179491.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-10-03
AI Technical Summary
In practical applications, existing transition metal electrocatalysts have cross-interference between anode and cathode catalysts, which reduces catalytic efficiency and stability. In addition, cobalt tungstate materials have low activity in hydrogen and oxygen evolution in water electrolysis, making it difficult to meet actual needs.
Phosphorus-modified cobalt tungstate bifunctional electrode materials were prepared by synthesizing phosphorus-modified cobalt tungstate nanoparticles on a nickel foam substrate. Sodium hypophosphite was used as a phosphorus source, and phosphorus modification was carried out in a tubular furnace to optimize the electronic structure of the material.
The dual-functional activity of cobalt tungstate materials in hydrogen and oxygen evolution in alkaline electrolytes is improved, the stability and performance of water electrolysis catalysts are enhanced, the production cost is reduced, and it is suitable for large-scale applications.
Smart Images

Figure CN120738699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis catalysts, and in particular to a phosphorus-modified cobalt tungstate bifunctional electrode material, a preparation method thereof, and an application thereof in water electrolysis to produce hydrogen. Background Art
[0002] Since the Industrial Revolution, the overconsumption of non-renewable energy sources such as coal, oil, and natural gas has led to increasingly serious environmental problems. In recent years, the Earth's climate system has continued to deteriorate, with various extreme weather events posing a serious threat to human survival. To address the climate crisis, a global energy system transformation is imperative in the coming decades. Hydrogen, as a renewable, clean energy source with zero carbon emissions, plays a vital role in this global energy transition. Water electrolysis based on renewable energy is a sustainable, large-scale approach to producing green hydrogen. However, the practical application of water electrolysis technology is limited by the sluggish kinetics of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Currently, precious metal-based materials are recognized as excellent water electrolysis catalysts. However, their limited Earth reserves hinder their large-scale application. Therefore, the development of abundant transition metal water electrolysis catalysts is needed. Currently, transition metal-based materials (such as sulfides and alloys) are widely developed as water electrolysis catalysts due to their unique electronic structures, abundant reserves, and excellent conductivity. However, the practical application of transition metal electrocatalysts still faces challenges. For example, during long-term industrial use, cross-interference between different cathode and anode catalysts can easily occur, reducing catalytic efficiency and stability. The development of highly efficient bifunctional catalysts for both hydrogen and oxygen evolution can effectively avoid this problem. Furthermore, bifunctional electrode catalysts not only effectively reduce catalyst costs but also simplify subsequent maintenance. Therefore, the development of highly active bifunctional catalysts is of great significance for the practical application of hydrogen production by water electrolysis.
[0003] In recent years, transition metal tungstate materials (such as cobalt tungstate) have attracted considerable attention in the electrochemical field due to their advantages, including large Earth reserves, low cost, corrosion resistance, and environmental friendliness. Practice has demonstrated their promising development prospects in electrochemical applications such as supercapacitors, lithium-ion batteries, sodium-ion batteries, and electrochemical sensors. However, in the field of electrocatalytic water splitting to produce hydrogen, the electrocatalytic HER and OER activities of cobalt tungstate catalysts have not yet met practical requirements. Therefore, this paper aims to improve the catalytic performance of tungstate materials by designing and manipulating their structure. However, the bifunctional activity of existing reported tungstate catalysts in alkaline media still lags significantly behind that of the precious metals Pt and RuO2, and further improvement is needed. Summary of the Invention
[0004] The purpose of the present invention is to solve the problem that in practical applications of existing transition metal electrocatalysts, cross-interference is easily generated between different catalysts in the anode and cathode, thereby reducing catalytic efficiency and stability. Transition metal tungstate materials have disadvantages such as low hydrogen and oxygen evolution activities in water electrolysis. A phosphorus-modified cobalt tungstate bifunctional electrode material and a preparation method are provided, as well as its application in hydrogen production by water electrolysis.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions: The invention discloses a phosphorus-modified cobalt tungstate bifunctional electrode material. The electrode material is obtained by synthesizing phosphorus-modified cobalt tungstate nanoparticles on a nickel foam substrate.
[0006] The size of the phosphorus-modified cobalt tungstate nanoparticles in the present invention is 2-5 μm.
[0007] The P element in the electrode material of the present invention is 2% to 6% of the total number of atoms of Co, W, O and P, preferably 4% to 5%.
[0008] The present invention also provides a method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material, comprising the following steps: (1) Pretreatment: Wet the surface of the substrate with anhydrous ethanol, let it dry naturally, then soak it in a dilute hydrochloric acid solution to remove surface impurities, then wash it with water and anhydrous ethanol in sequence, and dry it naturally before use; (2) Hydrothermal reaction: dissolve cobalt salt and tungstate in deionized water to obtain a hydrothermal reaction solution, then immerse the pretreated substrate material in the hydrothermal reaction solution for hydrothermal reaction. After the reaction is completed, take out the product, rinse it with deionized water and dry it naturally to obtain cobalt tungstate hydrate (COW); (3) Phosphorus modification: In a tube furnace, sodium hypophosphite was used as the P source, and cobalt tungstate hydrate (COW) was used as the modified substance. The temperature was raised to 450 °C at a rate of 5 °C / min under nitrogen or Ar atmosphere and the reaction was kept at this temperature for 2 h. The phosphorus source was provided by the decomposition of sodium hypophosphite, and then phosphorus modification was carried out on COW by chemical vapor deposition to obtain phosphorus-modified cobalt tungstate bifunctional electrode material (P-COW).
[0009] According to the above scheme, the cobalt salt in step (2) is cobalt nitrate with a concentration of 0.01~1.20 mol / L; the tungstate is ammonium metatungstate with a concentration of 0.001~0.50 mol / L; the temperature of the hydrothermal reaction is 120~180°C, and the time is 1~15 h.
[0010] According to the above scheme, the amount of sodium hypophosphite used in step (3) is 0.1~2.5 g.
[0011] The present invention also provides an application of a phosphorus-modified cobalt tungstate bifunctional electrode material in hydrogen production by electrolysis of water.
[0012] The present invention prepares a phosphorus-modified cobalt tungstate bifunctional electrode material by first synthesizing cobalt tungstate hydrate on a pretreated substrate material and then treating it with sodium hypophosphite. Cobalt tungstate materials themselves have few catalytic sites and poor hydrogen and oxygen evolution activities. The phosphorus-modified cobalt tungstate nanoparticles designed in the present invention have a larger specific surface area and, after phosphorus modification, increase their intrinsic hydrogen and oxygen evolution activities.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The phosphorus-modified cobalt tungstate nanoparticle electrode material (P-COW) provided by the present invention optimizes the electronic structure of the material by the P element, thereby having excellent HER and OER bifunctional activity and stability in alkaline electrolytes, promoting the development of high-performance bifunctional catalysts for water electrolysis.
[0014] (2) The phosphorus-modified cobalt tungstate nanoparticle electrode material of the present invention only requires a simple hydrothermal reaction and tubular furnace calcination method. The raw materials for preparation are cheap and easily available, and the synthesis is simple. Therefore, the electrolytic material can be produced on a large scale at low cost, which is conducive to the large-scale application of hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 XRD patterns of the NF prepared in Comparative Example 1 and the COW material prepared in Comparative Example 2; Figure 2 This is the XRD pattern of the P-COW material prepared in Example 3 of the present invention; Figure 3 This is the SEM image of the NF material prepared in Comparative Example 1; Figure 4 is an SEM image of the COW material prepared in Comparative Example 2; Figure 5 This is an SEM image of the P-COW electrode material synthesized in Example 3 of the present invention; Figure 6 TEM image of the P-COW electrode material synthesized in Example 3 of the present invention; Figure 7 This is an elemental surface scan of the P-COW electrode material synthesized in Example 3 of the present invention using energy dispersive X-rays; Figure 8 Co 2p high-resolution energy spectra of COW and P-COW electrode materials synthesized in Comparative Example 2 and Example 3 of the present invention; Figure 9 W 4f high-resolution energy spectra of COW and P-COW electrode materials synthesized in Comparative Example 2 and Example 3 of the present invention; Figure 10 This is a high-resolution P 2p spectrum of the P-COW electrode material synthesized in Example 3 of the present invention; Figure 11 The hydrogen evolution polarization curves of P-COW1, P-COW2, and P-COW electrode materials prepared in Examples 1-3 of the present invention in an alkaline freshwater electrolyte (1 M KOH) are shown; Figure 12 The oxygen evolution polarization curves of P-COW1, P-COW2, and P-COW electrode materials prepared in Examples 1-3 of the present invention in an alkaline freshwater electrolyte (1 M KOH) are shown; Figure 13 The hydrogen evolution polarization curves of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3 in alkaline fresh water electrolyte (1 M KOH) are shown; Figure 14 The oxygen evolution polarization curves of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3 in alkaline fresh water electrolyte (1 M KOH) are shown; Figure 15 The output of 10 mA / cm2 of the P-COW electrode material and other HER catalysts in alkaline fresh water electrolyte in Example 3 of the present invention is 2 Required overpotential diagram; Figure 16 The output of 10 mA / cm2 of the P-COW electrode material and other OER catalysts in alkaline fresh water electrolyte in Example 3 of the present invention is 2 Required overpotential diagram; Figure 17 Electrochemical double layer capacitors of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3; Figure 18 ECSA-normalized hydrogen evolution polarization curves of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3; Figure 19 ECSA-normalized oxygen evolution polarization curves of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3; Figure 20 Electrochemical impedance spectroscopy of hydrogen evolution in alkaline fresh water electrolyte (1 M KOH) for NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3; Figure 21 Electrochemical impedance spectroscopy of oxygen evolution of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3 in alkaline freshwater electrolyte (1 M KOH); Figure 22 This is a graph showing the hydrogen evolution stability test of the P-COW electrode material prepared in Example 3 of the present invention in an alkaline aqueous electrolyte (constant current test 100 mA / cm 2 ); Figure 23 The oxygen evolution stability test diagram of the P-COW electrode material prepared in Example 3 of the present invention in alkaline aqueous electrolyte (constant current test 100 mA / cm 2 ). DETAILED DESCRIPTION
[0016] In order to make the technical solution of the present invention more easily understood, the principles and features of the present invention will be described below in conjunction with specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0017] The substrate material used in the comparative examples and examples of the present invention is nickel foam with a purity of 99.9 wt%, a thickness of 0.15 cm, a size of 2x4 cm, a pore size of 100 ppi, a porosity of 98%, and an area density of 500 g / m 2 All drugs used were of analytical grade. Example 1
[0018] The method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material of this embodiment includes the following steps: (1) Pretreatment: Wet the surface of nickel foam (4 cm × 2 cm) with anhydrous ethanol, let it dry naturally, and then soak it in dilute hydrochloric acid solution to remove impurities in the surface oxide layer. Then wash it with water and anhydrous ethanol in sequence, and dry it naturally before use. (2) Hydrothermal reaction: Weigh 0.669 g of ammonium metatungstate and 0.654 g of cobalt nitrate and dissolve them in deionized water to obtain a hydrothermal reaction solution, wherein the concentration of ammonium metatungstate is 0.0045 mol / L and the concentration of cobalt nitrate is 0.028 mol / L; then place the pretreated metal nickel foam into the inner liner of a high-pressure reactor, and then place the high-pressure reactor into a thermostat, set the temperature to 160 ° C and react at this temperature for 9 hours. After the reaction is completed, wait for the thermostat to slowly cool to room temperature (about 30 ° C), take out the product, rinse it with distilled water for 5 minutes, and dry it naturally to obtain cobalt tungstate hydrate (COW); (3) Phosphorus modification: In a tubular furnace, the dried COW cobalt tungstate hydrate was placed in the middle of the tubular furnace, 0.5 g of sodium hypophosphite was weighed and placed at the upper air inlet, and the sodium hypophosphite was decomposed to provide a phosphorus source. The temperature was raised to 450 °C at a rate of 5 °C / min under nitrogen or Ar atmosphere and the reaction was carried out at a constant temperature for 2 h. After the reaction was completed, the tubular furnace was slowly cooled to room temperature to obtain a phosphorus-modified cobalt tungstate bifunctional electrode material (P-COW1). Example 2
[0019] The preparation method of a phosphorus-modified cobalt tungstate bifunctional electrode material (P-COW2) in this embodiment is similar to that in Example 1, except that 2.5 g of sodium hypophosphite is used as the phosphorus source. Example 3
[0020] The preparation method of a phosphorus-modified cobalt tungstate bifunctional electrode material (P-COW) in this embodiment is similar to that in Example 1, except that 0.8 g of sodium hypophosphite is used as the phosphorus source.
[0021] Comparative Example 1 The nickel foam base material (NF) of this comparative example is prepared as follows: Wet the surface of the nickel foam with anhydrous ethanol, let it dry naturally, and then soak it in a dilute hydrochloric acid solution to remove impurities in the surface oxide layer. Then wash it with water and anhydrous ethanol in turn, dry it naturally and set it aside.
[0022] Comparative Example 2 A cobalt tungstate hydrate (COW) material of this comparative example is prepared as follows: (1) Pretreatment: Wet the surface of nickel foam (4 × 2 cm) with anhydrous ethanol, let it dry naturally, and then soak it in dilute hydrochloric acid solution to remove impurities in the surface oxide layer. Then wash it with water and anhydrous ethanol in sequence, and dry it naturally before use. (2) Hydrothermal reaction: Weigh 0.669 g of ammonium metatungstate and 0.654 g of cobalt nitrate and dissolve them in deionized water to obtain a hydrothermal reaction solution, wherein the concentration of ammonium metatungstate is 0.0045 mol / L and the concentration of cobalt nitrate is 0.028 mol / L; then place the pretreated metal nickel foam into the inner liner of a high-pressure reactor, and then place the high-pressure reactor into a thermostat, set the temperature to 160 ° C and react at this temperature for 9 hours. After the reaction is completed, wait for the thermostat to slowly cool to room temperature (about 30 ° C), take out the product, rinse it with distilled water for about 5 minutes, and dry it naturally to obtain cobalt tungstate hydrate (COW).
[0023] The nickel foam substrate (NF) of Comparative Example 1 and the cobalt tungstate hydrate (COW) synthesized in Comparative Example 2 were subjected to XRD tests. Figure 1 As shown in Figure 2, the diffraction peaks of the cobalt tungstate hydrate COW synthesized in Comparative Example 1 match those of Ni (PDF#04-0850). 21 The diffraction peak of (OH)2·4H2O (PDF#47-0142) matches that of COW, which indicates that the crystal phase of the COW material generated after the hydrothermal reaction is cobalt tungstate hydrate material.
[0024] Figure 2From the XRD pattern of the P-COW material synthesized in Example 3 of the present invention, it can be found that except for the diffraction peak of Ni (PDF#04-0850) from the substrate, the other diffraction peaks of the synthesized catalyst after calcination in a tubular furnace and P treatment match the diffraction peaks of the standard substance CoWO4 (PDF#15-0847), indicating that the P-COW material generated after phosphorus modification is a cobalt tungstate material.
[0025] The NF of Comparative Example 1 was subjected to electron microscope scanning, and the results were as follows: Figure 3 As shown in the figure, scanning electron microscopy revealed that the nickel foam substrate has a three-dimensional skeleton morphology and a relatively smooth surface.
[0026] The COW synthesized in Comparative Example 2 was analyzed by electron microscope. Figure 4 As shown in the figure, scanning electron microscopy revealed that cobalt tungstate hydrate nanoparticles with a size of 2 to 5 μm were grown on the nickel foam substrate after the hydrothermal reaction.
[0027] The P-COW electrode material synthesized in Example 3 was subjected to electron microscope scanning, and the results were as follows: Figure 5 As shown in Figure 3, the structure of P-COW nanoparticles was also well preserved after calcination with sodium hypophosphite.
[0028] Figure 6 The P-COW electrode material synthesized in Example 3 of the present invention was analyzed by high-resolution transmission electron microscopy. As shown in the figure, the interplanar spacing of the P-COW electrode material is 0.36 nm, corresponding to the (110) crystal plane of CoWO4. Figure 2 The XRD characterization results confirm each other.
[0029] Figure 7 This is an energy-dispersive X-ray elemental scan of the P-COW electrode material synthesized in Example 3. As shown, P, Co, and W are evenly dispersed throughout the P-COW nanoparticles, further demonstrating that the P element is uniformly incorporated into the COW nanoparticles.
[0030] The present invention also uses a photoelectron spectroscopy (XPS) to characterize the element bonding and electronic structure information of the material. Figure 8 The Co 2p high-resolution energy spectrum of the COW and P-COW electrode materials synthesized in Comparative Example 2 and Example 3 of the present invention. As shown in the fine XPS spectrum of Co 2p, the classic Co 2p can be observed near 781.18 and 797.88 eV for both COW and P-COW. 3 / 2 Peak and Co2p 1 / 2 After P modification, the two spin-orbit doublet peaks of Co 2p are 1.3 eV (Co 2p 3 / 2 ) and 0.8 eV (Co 2p1 / 2 This may be because P modification causes part of the electrons of Co to be transferred to P with stronger electronegativity, thereby regulating the electronic structure of CoWO4.
[0031] Figure 9 The W 4f high-resolution energy spectrum of the COW and P-COW electrode materials synthesized in Comparative Example 2 and Example 3 of the present invention is shown in the fine XPS spectrum of W 4f. Both COW and P-COW have the classic W 4f 5 / 2 Peak and W 4f 3 / 2 After P modification, the peaks shifted to the high binding energy direction by 0.8 and 0.71 eV, respectively, which further proved that the modification of P atoms regulated the inherent electronic structure of CoWO4.
[0032] Figure 10 The P 2p high-resolution spectrum of the P-COW electrode material synthesized in Example 3 of the present invention shows a distinct PO peak at 133.28 eV, derived from the PO chemical bonds of the surface oxide. Furthermore, a PM peak was detected at 129.58 eV, indicating that the P atoms, after being introduced into the lattice, further form chemical bonds with the metal. Application Examples
[0033] In order to highlight the application effect of the P-COW electrode material prepared in the embodiment of the present invention, the materials synthesized in Examples 1-3 and Comparative Examples 1-2 were respectively subjected to electrolysis water performance tests. The electrochemical properties of various materials were tested in a PARSTAT MC multi-channel electrochemical workstation using a three-electrode system. In the three-electrode system, the materials synthesized in Examples 1-3 and Comparative Examples 1-2 were used as working electrodes, and graphite rods and mercury / mercuric oxide electrodes were used as counter electrodes and reference electrodes, respectively. The electrolysis water test used a 1 MKOH deionized water solution. The voltage measured by the electrochemical workstation was calculated using the following formula: E RHE = E Hg / HgO + 0.0591 × pH + 0.098 was converted to a universal reversible hydrogen electrode potential. Hydrogen evolution polarization curves were measured using linear voltammetry in the voltage range of 0.075 V to -0.625 V at a scan rate of 2 mV / s. Oxygen evolution polarization curves were measured using linear voltammetry in the voltage range of 1.155 V to 1.775 V at a scan rate of 2 mV / s.
[0034] Figure 11The hydrogen evolution polarization curves of the P-COW1, P-COW2, and P-COW electrode materials prepared in Examples 1-3 of the present invention in an alkaline freshwater electrolyte (1M KOH) are shown in the figure. As shown in the figure, the test results show that when the amount of sodium hypophosphite used is 0.8g, that is, the material in Example 3 exhibits the best electrocatalytic HER performance, with an overpotential of only 44 mV to output 10 mA / cm 2 The hydrogen evolution current density.
[0035] Figure 12 The oxygen evolution polarization curves of the P-COW1, P-COW2, and P-COW electrode materials prepared in Examples 1-3 of the present invention in an alkaline freshwater electrolyte (1M KOH) are shown in the figure. As shown in the figure, the test results show that when the amount of sodium hypophosphite used is 0.8g, that is, the material in Example 3 exhibits the best electrocatalytic OER performance, with an overpotential of only 287 mV to output 10 mA / cm 2 Therefore, the P-COW of Example 3 was selected to carry out a series of tests and analyses.
[0036] Figure 13 The hydrogen evolution polarization curves of the NF, COW, and P-COW electrode materials prepared in Comparative Examples 1, 2, and Example 3 in alkaline freshwater electrolyte (1 M KOH) are shown. It can be seen that the nickel foam substrate (NF) has the worst HER performance. After hydrothermal growth of COW, the alkaline HER performance is improved, but a high overpotential of 113 mV is still required to output 10 mA / cm 2 The P-COW modified with P only needs an ultra-low overpotential of 44 mV to output 10 mA / cm 2 This indicates that after P modification fully optimizes the electronic structure of P-COW, its HER activity in alkaline water electrolysis is also greatly improved.
[0037] Figure 14 The oxygen evolution polarization curves of NF, COW, and P-COW electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 3 in alkaline freshwater electrolyte (1M KOH) are shown. It can also be seen that the nickel foam substrate (NF) has the worst OER performance, requiring an overpotential of 393mV to output 10 mA / cm 2 The performance of COW was improved after growth, but still required 350 mV. After further P modification, P-COW only required an ultra-low overpotential of 287 mV to output 10 mA / cm 2 This indicates that after P modification fully optimizes the electronic structure of P-COW, its OER activity in alkaline water electrolysis is also significantly improved.
[0038] Figure 15The P-COW electrode material and other HER catalysts in Example 3 of the present invention output 10 mA / cm in alkaline electrolyte. 2 Comparison of required overpotentials. It can be seen that most studied transition metal HER materials require a high overpotential >70 mV, while the P-COW of the present invention only requires an ultra-low overpotential of 44 mV, even outperforming the precious metal Pt. Therefore, the HER performance of the P-COW electrode material of the present invention is very excellent.
[0039] Figure 16 The output of 10 mA / cm2 of the P-COW electrode material and other OER catalysts in alkaline electrolyte in Example 3 of the present invention is 2 Comparison of required overpotentials. It can be seen that the P-COW electrode material outperforms most studied transition metal OER materials, requiring only a low overpotential of 287 mV, and even outperforms the precious metal RuO2. Therefore, the P-COW electrode material of the present invention also exhibits excellent OER performance.
[0040] In order to further evaluate the intrinsic HER activity of the prepared materials, the present invention characterized and calculated the double-layer capacitance (C dl ), because the electrochemically active surface area (ECSA) is related to the electric double layer capacitance (C dl ), so the double layer capacitance (C dl ) can calculate ECSA. Figure 17 As shown clearly, after P modification, the double layer capacitance of the material increases, and the C dl Increased to 57.34 mF / cm 2 , which indicates that the electrochemically active surface area of the material is also improved after modification.
[0041] In order to study the intrinsic HER and OER activities of the prepared materials, the hydrogen evolution and oxygen evolution curves were normalized using the electrochemical active area. Figure 18 and Figure 19 The normalized hydrogen and oxygen evolution polarization curves of NF, COW, and P-COW prepared in Comparative Example 1, Comparative Example 2, and Example 3 are shown in FIG. Figure 17 The results were normalized. As shown in the figure, the bifunctional activity of the P-COW material after normalization is still significantly better than that of NF and COW, indicating that the P modification has significantly enhanced its intrinsic activity after comprehensively optimizing the electronic structure of P-COW.
[0042] Figure 20 and Figure 21The electrochemical impedance spectroscopy (EIS) spectra of NF, COW, and P-COW electrode materials in hydrogen and oxygen evolution tests are shown. It can be seen that the P-COW electrode material has a faster interfacial charge transfer rate in both hydrogen and oxygen evolution, indicating that P modification comprehensively optimizes the catalytic activity of P-COW.
[0043] Figure 22 and Figure 23 The long-term hydrogen and oxygen evolution stability test diagrams of the P-COW material prepared in Example 3 of the present invention in alkaline aqueous electrolyte (constant current test @ 100 mA / cm 2 ). It can be seen that at 100 mA / cm 2 Under high current density of hydrogen and oxygen evolution, the P-COW material can operate stably for more than 100 h (continuous work for more than 4 days), indicating that the P-COW material of this application has good stability in hydrogen and oxygen evolution by water electrolysis.
[0044] Based on the above-mentioned structural and performance characterizations, the study found that P modification comprehensively optimized the electronic structure of P-COW and significantly improved its intrinsic HER and OER activities, thus giving the material excellent dual-functional water electrolysis performance.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A phosphorus-modified cobalt tungstate bifunctional electrode material, characterized by: The electrode material is obtained by using foamed nickel as a base material and synthesizing phosphorus-modified cobalt tungstate nanoparticles on the base material.
2. The phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 1, characterized in that: The size of the phosphorus-modified cobalt tungstate nanoparticles is 2-5 μm.
3. The phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 1, characterized in that: The P element in the electrode material accounts for 2% to 6% of the total number of atoms of Co, W, O and P, and preferably 4% to 5%.
4. The method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 1, wherein: The following steps are involved: (1) Pretreatment: Wet the surface of the substrate with anhydrous ethanol, let it dry naturally, then soak it in a dilute hydrochloric acid solution to remove surface impurities, then wash it with water and anhydrous ethanol in sequence, and dry it naturally before use; (2) Hydrothermal reaction: dissolve cobalt salt and tungstate in deionized water to obtain a hydrothermal reaction solution, then immerse the pretreated substrate material in the hydrothermal reaction solution for a hydrothermal reaction. After the reaction is completed, take out the product, rinse it with deionized water, and dry it naturally to obtain cobalt tungstate hydrate; (3) Phosphorus modification: In a tube furnace, sodium hypophosphite was used as the P source and cobalt tungstate hydrate was used as the modified substance. The temperature was raised to 450 °C at a rate of 5 °C / min under nitrogen or Ar atmosphere and the reaction was kept at this temperature for 2 h. The decomposition of sodium hypophosphite provided a phosphorus source, and then phosphorus modification was carried out on COW by chemical vapor deposition to obtain a phosphorus-modified cobalt tungstate bifunctional electrode material.
5. The method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 4, characterized in that: The cobalt salt in step (2) is cobalt nitrate, with a concentration of 0.01-1.20 mol / L; the tungstate is ammonium metatungstate, with a concentration of 0.001-0.50 mol / L.
6. The method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 120-180° C., and the time is 1-15 h.
7. The method for preparing a phosphorus-modified cobalt tungstate bifunctional electrode material according to claim 4, characterized in that: The amount of sodium hypophosphite used in step (3) is 0.1-2.5 g.
8. Use of a phosphorus-modified cobalt tungstate bifunctional electrode material according to any one of claims 1 to 3 in hydrogen production by water electrolysis.